Development of Ukrainian Black-and-White Dairy cattle × Holstein of different constitution types in postnatal ontogenesis - V. D. Fedak; O. I. Stadnytska; B. V. Gutyj; N. V. Nazaruk; M. I. Polulikh; O. O. Bezaltychna; N. Yu. Kibenko; O. B. Shevchenko; A. S. Fediaieva; V. M. Bratiuk; Kh. Ya. Leskiv (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки)
In our study, the objective was to examine the growth of body weight and linear development of crossbred heifers, in-calf heifers, and cows of the Ukrainian Black-and-White Dairy x Holstein breed with different constitution types from birth to 21 months of age. The body weight growth indicators of heifers with a high physiological-breeding index (experimental group) and a low index (control group) were studied in postnatal ontogenesis. At birth, the body weight of the control and experimental groups was almost identical, at 29.5 and 29.7 kg, respectively. Subsequently, at 3, 6, 12, 18, and 21 months of age, the heifers in the experimental group surpassed their control counterparts in this indicator by 5.12 %, 4.71 %, 3.34 %, 4.39 %, and 4.71 %, respectively. The live weight of the experimental heifers at 18 months was 397 kg, while the control group was 380.5 kg. The experimental and control group heifers had a live weight of 18 months higher than the breed standard (375 kg) by 5.92 % and 1.3 %, respectively. From birth to 18 months, the average daily gains in live weight for the experimental group heifers were 681 g, while those for the control group were 650 g. A similar pattern was observed from birth to 21 months of age. The crossbred in-calf heifers at 8–9 months of gestation surpassed the control counterparts in the main body measurements: height at the withers, height at the sacrum, chest depth, body length, chest width, width at the hip joints, width at the hooks, chest circumference behind the shoulders, and pastern girth by 4.39 %, 5.71 %, 3.88 %, 4.25 %, 2.65 %, 1.84 %, 1.29 %, 3.11 %, and 1.09 %, respectively. The crossbred first-calf cows at 2–3 months of lactation surpassed the control counterparts in height at the withers and sacrum, chest depth, body length, width at the hip joints, width at the hooks, and chest circumference by 1.34 %, 2.73 %, 3.03 %, 2.15 %, 1.23 %, 2.61 %, and 2.28 %, respectively. Regarding chest width and pastern girth, the first-calf cows in the control and experimental groups had identical measurements. Therefore, based on the main body measurements, the heifers at different ages, in-calf heifers, and first-calf cows in the experimental group had an advantage over the control counterparts. There was no significant difference in the leg length index between the experimental and control counterparts. Regarding the stretch index, the experimental heifers at 12 months of age and cows at 2–3 months of lactation surpassed the control counterparts by 1.93 % and 0.79 %, respectively. In all other age periods of the heifers (3, 6, 18 months) and in-calf heifers (at 8–9 months of gestation), the advantage of the control animals over the experimental ones in the mentioned index was insignificant. Thus, regarding body weight growth and linear development, animals with a high physiological-breeding index outperformed those with a low physiological-breeding index in postnatal ontogenesis by 9–11 %.